Understanding the Quorum-Sensing Bacterium Pantoea stewartii Strain M009 with Whole-Genome Sequencing Analysis - Tan, Wen Si; Chang, Chien Yi; Yin, Wai Fong; Chan, Kok Gan (American Society for Microbiology, 2015)
Pantoea stewartii is known to be the causative agent of Stewart's wilt, which usually affects sweet corn (Zea mays) with the corn flea beetle as the transmission vector. In this work, we present the whole-genome sequence of Pantoea stewartii strain M009, isolated from a Malaysian tropical rainforest waterfall.